Reading in the book “Scientific Documentation: A Guide to Scientific Publishing (Arab Journal of Forensic Sciences & Forensic Medicine, 2020)
This research sheds light on the book "The Scientific Publication Guide" prepared by the American Psychological Association in the English language, and translated into Arabic by Professor Dr. Dhiyab Al-Badayneh. The book dealt with all the criteria, requirements and principles of publishing followed in the association's journals. The researcher pointed out that despite what was written about the principles of scientific research and its requirements in the Arabic language; the Arab Library still needs specialized evidence dealing with the standards, requirements and publishing principles in a number of scientific disciplines to put an end in the differences in views followed in the conditions for publication, its origins, and requirements in many Arab publishers.